Diversity and Interactions of the Naso-Buccal Bacteriome in Individuals with Allergic Rhinitis, Asthma and Healthy Controls - Marcos Pérez-Losada (Allergies)
Allergic rhinitis and asthma are significant public health concerns worldwide. While previous studies have explored how nasal and buccal bacteriotas influence these conditions, few have directly compared their bacteriomes within the same cohort. To bridge this gap, I analyzed 16S rRNA next-generation sequencing data from 347 individuals, including participants with allergic rhinitis, asthma and healthy controls. The nasal and buccal bacteriomes shared all dominant bacterial taxa but differed significantly in their phylum- and genus-level relative abundances. Alpha-diversity was significantly higher in the buccal cavity, while beta-diversity varied significantly across all indices and clinical groups. Over 80% of the predicted metabolic pathways were differentially regulated between the two cavities, yet these functional differences remained fairly consistent across clinical groups. Naso-buccal bacterial networks exhibited striking differences in structure, complexity and hub nodes. Notably, the network of healthy controls showed a clear segregation between nasal and buccal bacteria, with 93.5% of the interactions occurring within each respective cavity, and contained few pathogenic keystone taxa. In contrast, bacterial networks from diseased individuals exhibited reduced ecological specialization and more pathogenic keystone taxa linked to airway disease. These findings, thus, demonstrate that the naso-buccal bacteriome plays distinct yet interconnected roles in allergic rhinitis and asthma.